Uji Aktivitas Antoksidan dan Senyawa Fitokimia pada Tanaman Terung Pokak (Solanum torvum) - Helilusiatiningsih, Nunuk (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 6 No 1 (2021)DO - 10.24843/JITPA.2021.v06.i01.p01, 2021)
Pokak eggplant fruit in Indonesia was quite abundant as a wild plant. The research aimed to test antioxidant activity and phytochemical compounds of Pokak eggplant plant. The research method used quantitative analysis: DPPH and phytochemical moisture content. The results are fresh fruit research results: water content 82.2%, ash content 1.64%, protein 9.77%, fat 4.63%, carbohydrates 4.54%, Vitamin C 3.78%, phenol 33.95 mg/g, Tannins 0.94 mg/g, Flavonoids 1,38 mg/g, DPPH 85.58%. Seeds: water content 39.90%, ash 1.16%, protein 6.22%, fat 0.48%, carbohydrates 52.97%, Vitamin C 2.46%, phenol 21.84 mg/g, Tannins 0.52 mg/g, Flavonoids 2.32 mg/g, DPPH 86.88%. Dry stem: water content 6.88%, ash content 7.92%, protein 14.28%, fat 6.90%, carbohydrate 64.02%, Vitamin C 0.13%, phenol 92.14 mg/g, Tannin 1.61 mg/g, Flavonoids 8.04 mg/g, DPPH 78.47%. Fruit skin: water content 58.16%, ash content 0.26%, protein 5.74%, fat 0.32%, carbohydrates 35.29%, Vitamin C 1.34%, phenol 25.53 mg/g, Tannins 0.53 mg/g, Flavonoids 2.76 mg, DPPH 85.49%. Fresh Leaves: water content 58.16%, ash content 0.26%, protein 5.74%, fat 0.32%, carbohydrates 35.29%, Vitamin C 1.34%, phenol 25.53 mg/g, Tannins 0.53 mg/g, Flavonoids 2.76 mg/g, DPPH 85.49%. Dried Leaves: water content 7.52%, ash content 7.52%, protein 25.84%, fat 3.67%, carbohydrates 50.52%, Vitamin C 1.31%, phenol 12.87 mg/g, Tannins 0.20 mg/g, Flavonoids 1.76 mg/g, DPPH 64.50%.